A Review of Bluetooth based Scatternet for Mobile Ad hoc Networks - Asaf, Khizra; Umer, Muhammad; Kashif, Muhammad; Talib, Ramzan; Khan, Irfan (International journal of advanced computer science & applications, 2017)
Bluetooth based networking is an emerging and promising technology that takes small area networking to an enhanced and better level of communication. Bluetooth specification supports piconet formation. However, scatternet formation remains open. The primary challenge faced for scatternet formation is the interconnection of piconets. This paper presents a review of the proposed approaches and the problems confronted for establishing scatternet for ad hoc networks specifically MANET. In this work, a comparison of the Blue layer algorithm with MMPI interface based algorithm on Bluetooth scatternet formation. The enhancement in the developed MMPI framework makes it a good option for scatternet applications.